Peran praktik teknologi Pendidikan bagi perkembangan ilmu komunikasi Pendidikan - Peramtasari, Sinta Dewi (Indonesian Journal of Learning and Instructional Innovation, 2023)
This article will discuss educational technology for the development of communication in theworld of education. The practical role and also the weaknesses and strengths in the world ofeducation. Education that is increasingly advanced in practice always has the role of technologythat cannot be separated. Because since the outbreak of the corona virus in 2020, the learningsystem in Indonesia has started to change completely from face-to-face to screen-to-screen.Even when this pandemic has subsided to become endemic, New Normal begins to take effect.However, learning is actually increasingly in contact with screen-to-screen learning and isincreasingly digital. This is the turning point of our Education. In this case educationaltechnology has an important role in selecting, creating, and developing suitable learning mediaaccording to the learning needs and the character of the learner. The role of educationaltechnology is to facilitate learning and improve learning outcomes. So in this article we willalso discuss about this role. This article uses the library research method. (library research).